Recent developments in biological aspects of chalcones: the odyssey continues. (4th March 2019) - Rani, Anu; Anand, Amit; Kumar, Kewal; Kumar, Vipan
ABSTRACT: Introduction : Chalcones are attractive to synthetic chemists because they are easy to prepare, have a large number of replaceable hydrogens, thereby having significant biological potential. Chalcones and their derivatives (carbocyclic as well as heterocyclic) exhibit a range of biological properties including anticancer, antimalarial, antioxidant, anti-inflammatory and anti-tubercular activities. Their promising biological profile, along with their ease of synthetic manipulations, have triggered the design and development of new chalcone derivatives as well as their conjugates with active pharmacophores affording therapeutic templates targeting various diseases. Areas covered : This review focuses on synthesized substituted chalcones as well as chalcone-based molecular conjugates that have been developed between 2015 and 2018. Furthermore, their structure–activity relationships with an emphasis on their mechanism of action and docking studies along with their future therapeutic applications. Expert opinion : A recent upsurge in scientific literature encompassing the synthesis of new chalcone-derivatives as well as its role in ameliorating the activity profiles via amalgamation with other pharmacophores has clearly established the importance of chalcones in present-day drug discovery. As a point, we, the authors, believe that new effective scaffolds can be developed from chalcones with an added advantage of being available at a low cost.